PERAN KOMUNIKASI ORANGTUA DALAM MENGHADAPI EMOSI PADA ANAK DI DESA PEKUBUAN TANJUNG PURA LANGKAT - Juli Yanti Harahap; Vera Kristiana; Dina Hidayati Hutasuhut (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve parents' understanding and communication skills in dealing with children's emotions in Pekubuan Village, Tanjung Pura District, Langkat Regency. Problems faced by partners include parents' low understanding of children's emotional development, ineffective communication patterns, and high levels of negative emotional behavior in children such as tantrums and aggressiveness. The implementation method uses a participatory approach through stages of socialization, education, mentoring, and evaluation. The results of the activity show a significant increase in parents' understanding (from 45% to 85%) of communication skills and a decrease in negative emotional behavior in children and provide parents with direct experience in dealing with children's emotional situations. This activity has proven effective in building positive communication patterns that support the emotional development of children in the village.